Bariatric surgery modifies the bacterial diversity and metabolites of the gut microbiota by improving the metabolic profile of the host and contributing to weight reduction - Vigil-Guerrero, Roberto E. (2021)
Obesity is a chronic multifactorial disease with inflammatory characteristics that affects both sexes and all ages worldwide, increasing morbidity and mortality from various diseases. Obesity is associated with dysbiosis of the gut microbiota, thereby altering nutrient absorption and energy metabolism. Bariatric surgery has proven to be the best treatment for morbid obesity and diseases associated with overweight. Studies of the effects of bariatric surgery on the gut microbiota conducted in the last five years were characterized by a small number of subjects in the samples and a follow-up between 6 months and 1 year, with heterogeneous results. In general, bariatric surgery produces important changes in the intestinal microbiota, with an increase in Proteobacteria, Fusobacteria and Verrucomicrobia phyla; and decrease of the phylum Firmicutes. Akkermansia muciniphila it can be a key bacteria associated with the benefits obtained by surgery. The bacterial diversity increases from 6 months after surgery, and the final composition of the microbiota, after a period of adaptation, is associated with little energy release and detox-redox profile in the bacterial metabolism. No proven causal relationship between changes in the microbiota due to surgery and the beneficial effects in the host, although fecal material transplantation studies suggest a true phenotypic transfer associated with weight and metabolic profile. Knowing the mechanisms of this microbiota-host relationship would help to find therapeutic interventions with the same results that are obtained with surgery. In conclusion, bariatric surgery induces important changes in the gut microbiota, where bacterial metabolites interact with the host by improving metabolic profile and contributing to weight loss.